Relationship between Anisotropic Diffusion Properties and Tissue Morphology in Porcine TMJ Disc - Shi, Changcheng (2013)
OBJECTIVE: To investigate the relationship between anisotropic solute diffusion properties and tissue morphology in porcine temporomandibular joint (TMJ) discs. DESIGN: TMJ discs from eleven pigs aged 6–8 months were divided into five regions: anterior, intermediate, posterior, lateral, and medial. The transport properties and tissue morphology were investigated in three orthogonal orientations: anteroposterior, mediolateral, and superoinferior. The anisotropic diffusivity of fluorescein (332 Da) in the right discs was determined by the fluorescence recovery after photobleaching (FRAP) protocols. The tissue morphology in the left discs was quantified by scanning electron microscopy. RESULTS: The diffusivities of fluorescein in the TMJ disc were significantly anisotropic, except for the anterior region. In the medial, intermediate, and lateral regions, the diffusion along the fiber orientation (i.e., anteroposterior direction) was significantly faster than the diffusion in mediolateral and superoinferior directions. In the posterior region, the diffusion along the fiber orientation (i.e., mediolateral direction) was significantly faster than the diffusion in anteroposterior and superoinferior directions. The diffusion in the anterior region was mostly isotropic with the lowest degree of diffusion anisotropy, as well as collagen fiber alignment, likely due to the multi-directional fiber arrangement. The anterior region had the highest mean diffusivity [65.6 (49.3–81.8) μm(2)/s] in the disc, likely due to its high water content. The overall average diffusivity of fluorescein across the TMJ disc was 57.0 (43.0–71.0) μm(2)/s. CONCLUSIONS: The solute diffusion in porcine TMJ discs was strongly anisotropic and inhomogeneous, which associated with tissue structure (i.e., collagen fiber alignment) and composition (e.g., water content).